2011
DOI: 10.3357/asem.2977.2011
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Vestibular-Evoked Myogenic Potentials in Healthy Pilots and Student Pilots

Abstract: oVEMP should be interpreted with the AR rather than raw amplitude itself. Each institution should determine its own normal values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(39 reference statements)
0
2
0
1
Order By: Relevance
“…Similar findings of higher oVEMP amplitude in males than females are reported in oVEMP studies. 27,32 These differences were attributed to larger muscle bulk of inferior oblique muscles in males than females. 27…”
Section: Effect Of Sex On Mvemp Parametersmentioning
confidence: 99%
“…Similar findings of higher oVEMP amplitude in males than females are reported in oVEMP studies. 27,32 These differences were attributed to larger muscle bulk of inferior oblique muscles in males than females. 27…”
Section: Effect Of Sex On Mvemp Parametersmentioning
confidence: 99%
“…vague imbalance, "walking on foam", "feeling intoxicated", or newly developed visual vestibular mismatch) [15,16]. This symptom set has recently been classified as "visually induced dizziness" [17][18][19]. We found that in patients with abnormal VEMPs and normal caloric response, the horizontal calorics resulted in caloric responses greatly different to what would have been predicted in normals.…”
Section: Discussionmentioning
confidence: 87%
“…Η σύγκριση των διαφόρων παραμέτρων μεταξύ των δύο φύλων δεν ανέδειξε στατιστικά σημαντική διαφορά. Σε διάφορες μελέτες έχει σημειωθεί σημαντική διαφορά όσον αφορά στο πλάτος των δυναμικών, με υψηλότερες τιμές να παρατηρούνται σε άρρενα άτομα, γεγονός που μπορεί να οφείλεται στη διαφορά της μυϊκής μάζας μεταξύ αρρένων και θηλέων ατόμων(106,107).Σημαντικός περιορισμός της παρούσας μελέτης είναι το σχετικά μικρό δείγμα (100 άτομα, 200 αυτιά), εάν και θα πρέπει να σημειωθεί ότι το δείγμα είναι σημαντικά μεγαλύτερο σε σχέση με την πλειοψηφία των δημοσιευμένων μελετών.Επιπλέον, το δείγμα είναι κατανεμημένο περισσότερο σε μικρότερες ηλικίες, επηρεάζοντας μια ομοιόμορφη κατανομή. Τέλος, η καταμέτρηση των oVEMP αποτελεί μια σχετικά νέα μέθοδο, αυξάνοντας πιθανό bias λόγω της τεχνικής διενέργειας της εξέτασης, εάν και οι μετρήσεις πραγματοποιήθηκαν από άτομα με αξιόλογη εμπειρία στην καταγραφή προκλητών δυναμικών.ΣΥΜΠΕΡΑΣΜΑΤΑΣκοπός της παρούσας μελέτης ήταν να διευκολυνθεί η καθιέρωση φυσιολογικών τιμών για τη μέτρηση των oVEMP μετά από χορήγηση ηχητικών ερεθισμάτων tone burst 500 Hz αέρινης αγωγής, ώστε να επεκταθεί η διαγνωστική φαρέτρα στα πλαίσια της διαγνωστικής προσέγγισης για την εξέταση των ωτολιθοφόρων οργάνων του αιθουσαίου συστήματος.Από την ανάλυση των αποτελεσμάτων των καταγραφών των oVEMP εξάγονται τα ακόλουθα συμπεράσματα: 1.…”
unclassified